Nominal ellipsis as a collaborative effort - Ticio, Emma (Borealis – An International Journal of Hispanic Linguistics, 2016)
Following fundamental minimalist assumptions, this study aims to explain the distribution of nominal ellipsis (NE, henceforth) in Spanish as the result of last resort constraints at different components of the grammar. The current proposal is that NE in Spanish is a special case of trace deletion that results from the creation of an imperfect/defective/smaller copy, which must be interpreted as an anaphora (concretely, as a (definite) pronoun) at the semantic interface (hence, SEM) due to its ‘reduced’ size. Therefore, the structure created in narrow syntax will be interpreted as any other copy at the phonological interface (hence, PHON), where it is not pronounced, but it will be interpreted as a (definite) pronoun at SEM. This approach derives the partitive character of the NE construction and the impossibility of having NE with some Determiners and prenominal Adjectives as the result of an SEM clash between the presence of the anaphora and the meaning of the Determiner
Keywords: ellipsis; nouns; determiners; interfaces; features